2018
DOI: 10.1158/2326-6066.cir-18-0067
|View full text |Cite
|
Sign up to set email alerts
|

Improved Risk-Adjusted Survival for Melanoma Brain Metastases in the Era of Checkpoint Blockade Immunotherapies: Results from a National Cohort

Abstract: The successes of checkpoint blockade immunotherapy (CBI) and BRAF-targeted therapy trials have generated substantial promise for revolutionizing the management of patients with advanced melanoma. However, because early clinical trials of CBIs and BRAF-targeted therapy either excluded or included disproportionately fewer cases of melanoma brain metastases (MBMs), the survival benefit of these novel therapies for MBM remains unknown. We, therefore, evaluated the characteristics, management, and overall survival … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 38 publications
4
50
1
2
Order By: Relevance
“…Other investigations evaluating the role of immunotherapy using NCDB data have used similar date-based cutoffs to infer specific therapeutics used as standard-of-care for given diseases, or have assumed that immunotherapy consisted of checkpoint inhibitors. 42,[44][45][46] The only other NCDB study evaluating immunotherapy in SNM examined patients diagnosed from 2004 to 2015, without stratification based on time period or regard for changes in the definition of "immunotherapy." 42 Such an approach is unlikely to elucidate the role of checkpoint inhibition in this disease, as prior to 2011 the vast majority of immunotherapy likely consisted of other targeted agents.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigations evaluating the role of immunotherapy using NCDB data have used similar date-based cutoffs to infer specific therapeutics used as standard-of-care for given diseases, or have assumed that immunotherapy consisted of checkpoint inhibitors. 42,[44][45][46] The only other NCDB study evaluating immunotherapy in SNM examined patients diagnosed from 2004 to 2015, without stratification based on time period or regard for changes in the definition of "immunotherapy." 42 Such an approach is unlikely to elucidate the role of checkpoint inhibition in this disease, as prior to 2011 the vast majority of immunotherapy likely consisted of other targeted agents.…”
Section: Discussionmentioning
confidence: 99%
“…Combination of ICI treatment increases the risk of myocarditis as compared with single drug therapy. Given the early success of ICI in advanced cancer [17], we expect to see an increase of autoimmune diseases related to this novel drug class in the future [18].…”
Section: Definition Etiology and Epidemiologymentioning
confidence: 99%
“…Among them, the largest study was conducted by Iorgulescu et al . They conducted analysis on data, from the National Cancer Database, of 220,439 patients diagnosed with melanoma from 2010 to 2015, and found that in comparison to OS of 5.2 months for patients not treated with ICIs, immunotherapy lengthened OS to 12.4 months ( 10 ). In contrast, the number of prospective clinical trials in this field is small.…”
Section: Evidence Of Immunotherapy For Patients With Bmmentioning
confidence: 99%
“…Therefore, evidence regarding the use of ICIs in treating patients with BM is limited, and many questions remain unresolved. In some clinical studies, findings have suggested that ICIs are effective in enhancing the OS of patients with BM ( 10 , 11 ). However, the results have not been confirmed by a large prospective phase III clinical study.…”
Section: Introductionmentioning
confidence: 99%